2007
DOI: 10.1152/ajpheart.00022.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hemichannels in cardiomyocytes open transiently during ischemia and contribute to reperfusion injury following brief ischemia

Abstract: The aim of this study was to investigate changes in hemichannel activity during in vitro simulated ischemia [oxygen-glucose deprivation (OGD)] and the contribution of hemichannels to ischemia-reperfusion injury in rat neonatal cardiomyocytes. Dye uptake assays showed that hemichannels opened as OGD progressed, peaking after 1 h, and then closed, returning to the pre-OGD state after 2 h of OGD. The increase in dye uptake after 1 h of OGD was inhibited by hemichannel blockers (lanthanum chloride and a connexin 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(128 citation statements)
references
References 43 publications
7
121
0
Order By: Relevance
“…Inhibition of gap junctions during ischemia or reperfusion reduced infarct size (30,31), suggesting a possible protective effect by impeding spread of damaging metabolites via cell-cell contacts, which, however, remains controversial, given that ischemia, per se, initiates closure of gap junctions (32). Ischemia induces redistribution of Cx43 to the lateral wall of cardiomyocytes and may open these Cx43 hemichannels, which has been proposed to contribute to reperfusion injury (33)(34)(35). Notably, IP also suppresses gap junction permeability and induces Cx43 lateralization (31,33).…”
Section: See Retraction Published December 10 2012mentioning
confidence: 99%
“…Inhibition of gap junctions during ischemia or reperfusion reduced infarct size (30,31), suggesting a possible protective effect by impeding spread of damaging metabolites via cell-cell contacts, which, however, remains controversial, given that ischemia, per se, initiates closure of gap junctions (32). Ischemia induces redistribution of Cx43 to the lateral wall of cardiomyocytes and may open these Cx43 hemichannels, which has been proposed to contribute to reperfusion injury (33)(34)(35). Notably, IP also suppresses gap junction permeability and induces Cx43 lateralization (31,33).…”
Section: See Retraction Published December 10 2012mentioning
confidence: 99%
“…A Px1 mimetic peptide with apparent specific blocking effect was also recently reported ( 110 pxn1) (Pelegrin and Surprenant 2006). A large number of publications demonstrate specific effects of some of these peptides on connexin hemichannels by using in parallel scrambled peptide versions, additional hemichannel blockers and/or studies of their effects on connexin-specific expression systems (Braet et al 2003a(Braet et al , 2003bPearson et al 2005;Gomes et al 2005;Eltzschig et al 2006;Takeuchi et al 2006;DeVuyst et al 2006;De Vuyst et al 2007;Retamal et al 2006Retamal et al , 2007bShintani-Ishida et al 2007). However, it was recently reported that some Cx32, Cx43, and Px1 mimetic peptides cause non-specific blockade of hemichannels formed by Px1, Cx46, and a connexin Cx32 chimera carrying the first extracellular loop of Cx43 (Cx32E143) in the oocyte expression system (Wang et al 2007).…”
Section: Pharmacology Of Hemichannelsmentioning
confidence: 87%
“…1C). Previous studies have suggested that cardiomyocytes release ATP in response to cell stress via a variety of factors such as maxi-anion channels [7], cystic fibrosis transmembrane conductance regulator (CFTR) [17], and connexin and/or pannexin hemichannels [8,18]. In addition, in cultured astrocytes, mechanical stress to cells results in the release of ATP via exocytosis (vesicular ATP release) [19].…”
Section: Resultsmentioning
confidence: 99%
“…In neonatal rat cardiomyocytes, exposure of cultures to ischemic stress mimicked by oxygen-glucose deprivation (OGD) results in the release of ATP via maxi-anion channels [7]. In addition, Shintani-Ishida et al [8] have recently demonstrated that brief ischemic stress to neonatal cardiomyocytes transiently opens Cx43 hemichannels, leading to the release of ATP via hemichannels. At present, however, it is almost completely unknown whether the release of ATP from cardiomyocytes during ischemia is strictly regulated, and if so, how cardiomyocytes 5 regulate the release.…”
Section: Introductionmentioning
confidence: 99%